The European Company Statute in the context of freedom of establishment - Ringe, W (Hart, 2007)
One of the key features of the new Europeanwide legal form “European Company” (“Societas Europaea” or “SE”) is the possibility of transferring the company’s seat from one Member State to another without having to be wound up or to re-register. As this possibility does not exist for companies formed under national law, the formation of an SE will often present the only possibility for companies to transfer their incorporation and corporate headquarters between Member States. This is a big advantage and a milestone towards the European Internal Market. However, some doubts remain as to the practicability of the system. The mandatory linkage of the head office to the registered office within the same Member State according to Article 7 of the SE Regulation is very problematic and, in light of recent ECJ decisions such as Centros, Überseering, and Inspire Art, may violate EC primary legislation. Why should companies that are formed under national law be allowed to have the head office in a Member State different from their registration state, while an SE – as an instrument of Community Law and a symbol of the Internal Market – is not? Furthermore, the detailed procedural rules laid down in the Regulation are sometimes overprotective and may significantly reduce the attractiveness of the SE’s mobility. It is argued that Article 7 of the SE Regulation is secondary law that itself is inconsistent with the (primary) EC Treaty. Furthermore, the Member States also tend to be overprotective when enacting safeguard measures for the benefit of creditors, minority shareholders and employees. Here again, freedom of establishment does not allow protectionist measures that contravene the gist of the SE’s mobility.